Probing system size dependence at high baryon density by systematic comparison of Ag+Ag and Au+Au reactions at 1.23A GeV. (1st February 2023) - Reichert, Tom; Kittiratpattana, Apiwit; Li, Pengcheng; Steinheimer, Jan; Bleicher, Marcus
Abstract: We present UrQMD predictions for the comparison of the recently measured Ag+Ag and Au+Au runs at a beam energy of E lab = 1.23A GeV explored by the HADES experiment. To this aim, different centrality definitions are investigated: We suggest that in the case of particle production, both systems should be compared at the same number of participating nucleons, while for a comparison of the (elliptic) flow, a selection on the initial state eccentricity—as in high energy reactions—is better suited. Generally, we find good agreement between both systems, if these centrality criteria are used. Specifically, the deuteron yields per participant and the pion to proton ratios are shown to scale with A part except for very central Ag+Ag reactions due to stronger stopping in such reactions. The elliptic flow in both systems follows initial state eccentricity scaling, albeit with the opposite sign as compared to high energies, suggesting a strong relation between final flows and the initial state also at the low energies explored here. The observation of this scaling might then allow to obtain further information on the expansion properties (and the EoS) of matter at high baryon densities.